Linguistics and Society: an Interdisciplinary Perspective (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the dynamic relationship between linguistics and society, emphasizing how language functions not only as a system of communication but also as a social institution. It explores how language both reflects and constructs identity, reveals patterns of social stratification, and adapts to the pressures of globalization. Drawing on the works of scholars such as Labov, Baugh, and Lippi-Green, the discussion demonstrates that linguistic phenomena cannot be studied in isolation but must be situated within broader social, cultural, and political contexts. The findings suggest that the study of language is essential for understanding issues of social equity, cultural preservation, and global interconnectedness.